2009
DOI: 10.1007/s12185-009-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variations between affected siblings with ataxia-telangiectasia: ataxia-telangiectasia in Japan

Abstract: A nationwide survey was conducted for identifying ataxia-telangiectasia (AT) patients in Japan. Eighty-nine patients were diagnosed between 1971 and 2006. Detailed clinical and laboratory data of 64 patients including affected siblings were collected. Analyses focused on malignancy, therapy-related toxicity, infection, and hematological/immunological parameters. The phenotypic variability of AT was assessed by comparing 26 affected siblings from 13 families. Malignancy developed in 22% of the cases and was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
2
25
2
Order By: Relevance
“…Thus, future studies are needed to determine whether persistent MHV68 replication is sufficient to induce lung pathology in ATM-deficient mice, which, unlike humans with A-T, do not spontaneously develop lung disease. While A-T patients display altered anti-EBV antibody responses suggestive of persistent viral replication (4,22,36), the status of EBV infection is poorly understood, and it is not known whether EBV contributes to the lung disease observed in A-T patients. The clinical finding that steroids, but not antibiotic treatment, suppress or even reverse lung deterioration in A-T patients (33,40) suggests that chronic immune stimulation that may be driven in part by virus infections does contribute to lung disease in A-T. Future studies are needed to define the relative contribution of chronic virus infections to the development and progression of lung disease in A-T patients.…”
Section: Implications For A-t and Other Ddr-linked Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, future studies are needed to determine whether persistent MHV68 replication is sufficient to induce lung pathology in ATM-deficient mice, which, unlike humans with A-T, do not spontaneously develop lung disease. While A-T patients display altered anti-EBV antibody responses suggestive of persistent viral replication (4,22,36), the status of EBV infection is poorly understood, and it is not known whether EBV contributes to the lung disease observed in A-T patients. The clinical finding that steroids, but not antibiotic treatment, suppress or even reverse lung deterioration in A-T patients (33,40) suggests that chronic immune stimulation that may be driven in part by virus infections does contribute to lung disease in A-T. Future studies are needed to define the relative contribution of chronic virus infections to the development and progression of lung disease in A-T patients.…”
Section: Implications For A-t and Other Ddr-linked Diseasesmentioning
confidence: 99%
“…Importantly, A-T patients seem to be selectively susceptible to severe herpesvirus infections. In one study, herpesviruses were the cause of 8 out of 11 severe viral infections observed in A-T patients (36). It is not known whether herpesvirus infection contributes to lung disease or cancer observed in the A-T population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ATMdeficient hosts, whether humans or mice, are selectively susceptible to severe chronic, but not acute, viral infections. Specifically, A-T patients display elevated EBV and HHV-6 loads, have prolonged and exacerbated primary varicella-zoster virus infection, and display more robust and persistent skin lesions associated with human papillomavirus (HPV) infection (11)(12)(13)(14)(15)(16)(17). These observations contradict the well-established proviral phenotypes in tissue culture systems, where ATM facilitates infection and replication of diverse herpesviruses and HPV.…”
Section: Discussionmentioning
confidence: 95%
“…Intriguingly, in contrast to the proviral activity of ATM manifested in tissue culture, A-T patients are selectively susceptible to severe herpesvirus infections, including frequent complications of primary varicella-zoster virus infection (11)(12)(13)(14)(15)(16)(17). Further, EBV (and human herpesvirus 6 [HHV-6], when present) loads are significantly elevated in A-T patients, and abnormal EBV-driven lymphoproliferation observed early in life has been suggested as a possible diagnostic trigger for A-T (12).…”
mentioning
confidence: 99%